The missional church in perspective : mapping trends and shaping the conversation - Van Gelder, Craig; Zscheile, Dwight J., 1973- (Grand Rapids, Mich. : Baker Academic, 2011)
"In this book, two leading ministry experts place the missional church conversation in historical perspective and offer fresh insights for its further development. They begin by providing a helpful review of the genesis of the missional church and offering an insightful critique of the Gospel and Our Culture Network's seminal book Missional Church, which set the conversation in motion. They map the diverse paths this discussion has taken over the past decade, identifying four primary branches and ten sub-branches of the conversation and placing over one hundred published titles and websites into this framework. The authors then utilize recent developments in biblical and theological perspectives to strengthen and extend the conversation about missional theology, the church's interaction with culture and cultures, and church organization and leadership in relation to the formation of believers as disciples. Professors, students, and church leaders will value this comprehensive overview of the missional movement. It includes a foreword by Alan J. Roxburgh" -- Publisher description.
Concepts influencing the missional church conversation -- Revisiting the seminal work missional church -- Mapping the missional conversation -- Expanding and enriching the theological frameworks -- Missional engagement with culture in a globalized world -- Missional practices of church life and leadership.
Includes bibliographical references and index.
Keywords: Missional Church; Mission of the church